Gardner's art through the ages - Gardner, Helen; de la Croix, Horst; Tansey, Richard G. (California : Harcourt Brace Jovanovich College Publishers, 1986)
The goal of art history-the subject of this book-is the discerning appreciation and enjoyment of art, from whatever time and place it may have come, by whatever hands it may have been made. Outside the academic world, the terms art and history are not often juxtaposed. People tend to think of history as the record and interpretation of past (particularly political) human actions, and of art-quite correctly-as something present to the eye and touch, which of course, the vanished human events that make up history are not. The fact is that a visible and tangible work of art is a kind of persisting event. It was made at a particular time and place by particular persons, even if we do not always know just when, where, and by whom. Although it is the creation of the past, art continues to exist in the present, long surviving its times.
I. The Ancient World-- 1. The Birth of art-- 2. The Ancient near East-- 3. The Art of Egypt-- 4. The Art of the Aegean-- 5. The Art of Greece-- 6. Etruscan and Roman Art-- 7. Early Christian, Byzantine, and Islamic Art -- II. The Middle Ages-- 8. Early Medieval Art-- 9. Romanesque Art-- 10. Gothic Art -- III. The Non-European World-- 11. The art of India-- 12. The art of China-- 13. The art of Japan-- 14. The native arts of the Americas, Africa, and the South Pacific.
Includes bibliographical references and index.
Keywords: ART -- HISTORY